Framing risk governance. Issue 11 (25th October 2019) - Stein, Volker; Wiedemann, Arnd; Bouten, Christiane
Abstract : Purpose: The purpose of this paper is to apply the concept of framing in the field of risk governance and risk management research. Design/methodology/approach: A five-constituent approach to framing – cognitive, strategic, action, emotional and institutional framing – is applied to contrastively analyze the multifaceted character of the two concepts of risk governance and risk management. Findings: This paper analyzes the multifaceted utilization of risk governance framing and the conscious demarcation between risk governance and risk management. Risk governance framing strengthens the proactive control of strategic risks with regard to business model adaptation to changing risk landscapes. The verbal imagery of risk governance already sets the agenda for the sustainability-oriented as well as value-oriented steering of the risks of a business model. Following the analysis of the different framing areas, propositions are presented. Originality/value: Although framing is applied in various academic disciplines, there is limited research relating to corporate risks. While risk governance provides companies with a concept to ensure the sustainability of their business models in the complex risk landscape, the related framing brings the appropriate interpretation and the deliberate tone into focus.